Extracting the limiting factors in photocurrent measurements on TiO2 nanotubes and enhancing the photoelectrochemical properties by Nb doping - Özkan, Selda; Mazare, Anca Valentina; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work, we extract the key factors that influence and limit the photoresponse of anodic TiO2 nanotubular layers. For this we formed nanotube layers of different thicknesses, annealed the structures at different temperatures and evaluated the doping effect of Nb. Using various analytical characterization tools (SEM, XRD, XPS, ToF-SIMS), we found that a most crucial impact on limiting the photoresponse in nanotubular layers is the formation of a rutile layer at the metal/oxide interface during the thermal annealing process (by thermal oxidation of Ti metal underneath tubes). This rutile layer increases severely in thickness with annealing temperature. We show that this detrimental effect can be overcome by doping the TiO2 NTs with very low amounts of Nb (0.1 at% Nb), which can result in a 12-fold increase of the IPCE for high temperature annealed TiO2 NTs.
EAM Import::2019-03-14